(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
The main objective of this article is to socialize advances on a critical review of musical biography in Colombia and the rest of Latin America from musicology, to determine the current perspectives of parameters within their methodologies and narratives. The approach used here is qualitative research, through the critical review of sources with a view predominantly from historical musicology. The relevance of this article sustains in the opening of the expository and methodological canons that have emerged from musicology, thanks to the current challenges and questions proposed by researchers around the life stories of musicians, teachers, composers and managers within the territorial and local contexts of Latin America. The main conclusions regarding the clarity of some multidisciplinary theories and methodologies that can be adapted to the current perspective in Latin America would be those raised in this bibliographic review: by Waisman, “The decomposition of the subject into multiple, changing and contingent identities.” From González, the interrelation and constant dialogue of the macrostory with the microstories, creating the concept of “Located Popular Music” as a historical subject within musicology. From Merino and Musri, the musical work as text and production, circulation and reception as context. From Mesa, the network of connections between the different local, regional and national dynamics, at a historical and musical level. Of course from Madrid, the antibographical character that deconstructs and gives a new air to the biographical genre within musicology.